Measuring healthcare preparedness: an all-hazards approach - Marcozzi David E; Lurie Nicole (BMC, 2012)
Abstract In a paper appearing in this issue, Adini, et al. describe a struggle familiar to many emergency planners-the challenge of planning for all scenarios. The authors contend that all-hazards, or capabilities-based planning, in which a set of core capabilities applicable to numerous types of events is developed, is a more efficient way to achieve general health care system emergency preparedness than scenario-based planning. Essentially, the core of what is necessary to plan for and respond to one kind of disaster (e.g. a biologic event) is also necessary for planning and responding to other types of disasters, allowing for improvements in planning and maximizing efficiencies. While Adini, et al. have advanced the science of health care emergency preparedness through their consideration of 490 measures to assess preparedness, a shorter set of validated preparedness measures would support the dual goals of accountability and improved outcomes and could provide the basis for determining which actions in the name of preparedness really matter.